1992
DOI: 10.1159/000114124
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Cortex in Play Fighting by Rats: Developmental and Evolutionary Implications

Abstract: Play is a distinctive behavior of young mammals, especially mammals with a well-developed forebrain. For this reason it is thought that there may be a relation between forebrain evolution and highly elaborated play behavior. This study investigated the contribution of the cortex to play behavior by comparing play in control and neonatally decorticated rats (Rattus norvegicus). Play fighting in rats involves the combination of attack by one rat and defense by the recipient, with pinning arising when specific pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
109
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 10 publications
8
109
0
Order By: Relevance
“…Play behavior: Beside the frequency of play behaviors (pins, attacks, and defensive behavior) (Pellis et al, 1992;Pellis and McKenna, 1995;, the percentage of defensive behavior depending upon the number of attacks received was also evaluated (see Defense). We further analyzed the percentage of pins for an animal, initiated by its own complete rotation and also the probability to respond upon an attack.…”
Section: Behavioral Testingmentioning
confidence: 99%
See 3 more Smart Citations
“…Play behavior: Beside the frequency of play behaviors (pins, attacks, and defensive behavior) (Pellis et al, 1992;Pellis and McKenna, 1995;, the percentage of defensive behavior depending upon the number of attacks received was also evaluated (see Defense). We further analyzed the percentage of pins for an animal, initiated by its own complete rotation and also the probability to respond upon an attack.…”
Section: Behavioral Testingmentioning
confidence: 99%
“…Surprisingly, it was found that neonatally decorticated rodents still engage in play fights as juveniles (Panksepp et al, 1994;Pellis et al, 1992). These findings indicate that an intact cortex is not necessary for rats to engage in social play and, therefore, cannot be involved in the motivation of social play behavior (Pellis et al, 1992). However, decorticated rats showed a significant reduction in pinning, a common position in play fights in which one rat stands over a supine partner.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The transition from infancy to adulthood marks the ontogenesis of fundamental behavioral processes, such as threat learning (Rudy, 1993;Richardson et al, 2000;Akers et al, 2012;Deal et al, 2016), social interaction (Panksepp, 1981;Vanderschuren et al, 1997), and aggression (Pellis et al, 1992;Pellis and Pasztor, 1999). On the other hand, this period is also characterized by a peak incidence of the majority of psychiatric disorders (Kessler et al, 2005).…”
Section: Introductionmentioning
confidence: 99%